TURNING ART INTO VISION: PROSE, POETRY, PAINTING INTERFACE OF LANDSCAPE ARTISTS, AND IMPRESSIONISTS - Mukherjee, Pradipta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The paper discusses the interface of literature and painting through the prism of a 19th century art movement, better known as Impressionism. A movement in painting and literature, Impressionism stylistically made way for the beholder, listener, or reader to participate in recreating the experience of the artist. Its “new” method was to suggest the “impression” or effect on the artist rather than to make precise and explicit the objective characteristics of things and events. Emerging in France in the latter half of the 19th century with painters like Monet, Manet, Degas, Pissarro, Renoir and Cezanne, this art movement seems to have had a major impact on the world literary and cultural scene, facilitating and manifesting a symbiosis between sister arts, that is, painting and literature. To trace the gradual advent of Impressionism, the paper recounts the journey of English romantic landscape painters like Turner and Constable as we eventually reach the French Impressionists while concomitantly discussing how literary Impressionists, particularly modern novelists, deploy the stream-of-consciousness technique, and poets, often seen as “Symbolists” and “Imagists,” have contributed to the evolution of modernist literature and sensibilities.